Psychology and Behavioral Economics Lessons for the Design of a Green Growth Strategy - Weber, Elke U.; Johnson, Eric J. (World Bank, Washington, DC, 2013)
A green growth agenda requires policy makers, from local to supranational levels, to examine and influence behavior that impacts economic, social, and environmental outcomes on multiple scales. Behavioral and social change, in addition or conjunction with technological change, is thus a crucial component of any green growth strategy. A better understanding of how and why people consume, preserve, or exploit resources or otherwise make choices that collectively impact the environment has important and far-reaching consequences for the predictive accuracy of more sophisticated models, both of future states of the world and of the likely impact of different growth strategies and potential risk management strategies. The prevailing characterization of human decision making in policy circles is a rational economic one. Reliance on the assumptions of rational choice excludes from consideration a wide range of factors that affect how people make decisions and therefore need to be considered in predictions of human reactions to environmental conditions or proposed policy initiatives. In addition, a more complete and more fully descriptive understanding of decision processes provide powerful tools for policy design that complement legal or economic instruments or may lead to more effective implementation of such policy instruments.